Exploring Gen-Z Users’ Experiences of e-Service Quality Strategies in Shopee Marketplace: A Phenomenological Study - melvin zakri; Tasya Aspiranti; Muhardi; Arief Budiyanto (Jurnal Manajemen Bisnis dan Kesehatan, 2026)
This study explores the lived experiences of Generation Z users regarding e-service quality strategies in the Shopee marketplace in Indonesia. As digital natives, Gen-Z consumers engage with online services not only functionally but also emotionally and socially, redefining traditional understandings of service quality. The research aims to uncover how Gen-Z users perceive, interpret, and assign meaning to Shopee’s e-service quality dimensions within their daily interactions. Adopting a qualitative phenomenological approach, data were collected through in-depth semi-structured interviews with 14 active Shopee users aged 19–27 in the Greater Jakarta area. Data were analyzed using Moustakas’s phenomenological reduction combined with Braun and Clarke’s thematic analysis, resulting in six major themes: (1) digital convenience and efficiency, (2) emotional engagement through gamification, (3) trust and security in transactions, (4) social influence and community validation, (5) aesthetic and personalized experience, and (6) frustration and service recovery. The findings reveal that Gen-Z users perceive e-service quality as a holistic experiential construct—where emotional enjoyment, peer influence, and trust-based recovery play a pivotal role alongside functional performance. This study concludes that for Gen-Z, the essence of e-service quality lies in how the service feels, not merely how it functions. The research contributes to the theoretical expansion of e-service quality frameworks by emphasizing emotional and social dimensions and offers practical insights for marketplace managers to design more engaging, human-centered digital experiences.